Parenting styles and the mental health of left-behind children in China - Wu, Lingrui; Qi, Di (Frontiers in Psychology, 2025)
The issue of left-behind children is a prominent social challenge that has surfaced in recent years as China’s modernization process advances. Due to national policies and economic limitations, most migrant parents opt to leave their children behind in their hometowns and entrusted to other relatives. The prolonged absence of parents, inadequate caretaker ability of other relatives, and limited resources in communal living conditions lead to mental development problems in left-behind children to varying degrees. Such children are more vulnerable to depression, anxiety and loneliness compared to their peers. Thus, the mental health issues of left-behind children ought to receive requisite attention. This paper utilizes the 2013–2014 survey data from the China Education Panel Study (CEPS) for an empirical research aiming to analyze quantitatively the effect of parenting styles on mental health of left-behind children, along with an examination of the mediating role of mental resilience, the results of which are as follows: first, positive parenting behavior significantly reduces mental health problems among left-behind children, whereas positive parenting attitudes do not have a significant effect; second, mental resilience mediates the influence of parenting behavior on children’s mental health but not the effect of parenting attitudes; and third, both positive parenting behavior and parenting attitudes significantly enhance the mental resilience of left-behind children.